10 tips for choosing case-management software. - Bernstein, Paul (Trial: The National Legal Newsmagazine, 1995)
Ten tips are presented for honing selecting and user skills so that attorneys can choose the right case-management software for their office. Attorneys should be the master of their software; map out a plan to guide their acquisition of what they require; keep the product that they buy simple; know the “source code” that allows users to manipulate the features and functions of the software that they are using; ensure that the software that they intend to buy can handle discovery requirements and other aspects of casework; test out the product that they intend to buy; ensure that the case-management software provides or integrates with project planning or project management software; be cost-conscious but realistic; check out the vendor of the product that they intend to buy; and know what they require.